Architecture of Almoravid and Amohadism (comparative study) - Sarem , wafaa (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
The research in based on the study of Almoravid and Amohadism architecture and its impact on political conditions , these conditions , which led to the establishment of a marabit school, depend primarily on military architecture for political reasons and a school uniformed interest in shool and the a theist primarily because it depends on the basis of religious and political circumstamces surrounding it help them to do so. Therefore the historical situation of the Almoravids and the Amohadis was studied briefly to give a clear picture of what Almoravids and Amohadis and how they reached power and entered Andalusia. Then he studied the influence of the Andalusian architecture on the Almoravids and Amohadis architecture which appeared in the minarets and decorations, by iden tifying some models of there architecture , through the tow types converged, they differed from simple but distinct object, while the Almorvid architecture tended to be austerity , while Almohadism was characterizebdy luxury.